Cardiac modulation of startle is altered in depersonalization-/derealization disorder: Evidence for impaired brainstem representation of baro-afferent neural traffic. (30th June 2016) - Schulz, André; Matthey, Jan Hendrik; Vögele, Claus; Schaan, Violetta; Schächinger, Hartmut; Adler, Julia; Beutel, Manfred E.; Michal, Matthias
Abstract: Patients with depersonalization-/derealization disorder (DPD) show altered heartbeat-evoked brain potentials, which are considered psychophysiological indicators of cortical representation of visceral-afferent neural signals. The aim of the current investigation was to clarify whether the impaired CNS representation of visceral-afferent neural signals in DPD is restricted to the cortical level or is also present in sub-cortical structures. We used cardiac modulation of startle (CMS) to assess baro-afferent signal transmission at brainstem level in 22 DPD and 23 healthy control individuals. The CMS paradigm involved acoustic startle stimuli (105 dB(A), 50 ms) elicited 0, 100, 200, 300, 400 and 500 ms after a cardiac R-wave. In healthy control individuals, we observed lower startle responses at 100 and 300 ms than at 0 and 400 ms after an R-wave. In DPD patients, no effect of the cardiac cycle on startle response magnitude was found. We conclude that the representation of visceral-afferent neural signals at brainstem level may be deficient in DPD. This effect may be due to increased peripheral sympathetic tone or to dysregulated signal processing at brainstem level. Highlights: CNS representation of afferent bodily signals is altered in depersonalization (DPD). Cardiac modulation of startle (CMS) may reflect baro-afferent signals at brainstem. CMS was observed in healthy controls, but not in patients with DPD. Representation of visceral-afferent signals in DPD may be deficient at the brainstem.